Dr. Deniz Sarhaddi — Deep Plane Facelift — St. Louis - Sarhaddi, Deniz (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Deniz Sarhaddi, practicing in St. Louis, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003319; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; st. louis